Integration of process safety engineering and fire protection engineering for better safety performance. (September 2015) - Chen, Hao; Pittman, William C.; Hatanaka, Logan C.; Harding, Brian Z.; Boussouf, Adam; Moore, David A.; Milke, James A.; Mannan, M. Sam
Abstract: Since the inception of the process industries, there have been a great number of process incidents causing significant loss of life and property damage. Even the establishment and implementation of a series of rigorous regulations has not prevented the occurrence of process incidents. In order to protect people, property and the environment a more robust safety program is needed and the safety performance of process industries must continue to improve. In this work, the common ground and the unique characteristics of process safety engineering (PSE) and fire protection engineering (FPE) is reviewed to demonstrate the potential benefits of unifying the two fields or improving the coordination between them to create a more robust safety program, thereby enhancing the safety performance of process industries. Recommendations are made to facilitate and encourage continued discussion and efforts toward the integration of process safety engineering and fire protection engineering. Highlights: Background information of process safety engineering (PSE) and fire protection engineering (FPE) is reviewed. The common ground between PSE and FPE and their unique characteristics are elaborated. The integration of PSE and FPE to establish a more robust safety program is proposed and discussed.